Gas Nanosensors Based on Individual Indium Oxide Nanostructures. (2015) - Domènech-Gil, Guillem; Samà, Jordi; Pellegrino, Paolo; Barth, Sven; Gràcia, Isabel; Cané, Carles; Romano-Rodriguez, Albert
Abstract: Indium oxide nanowires have been fabricated via carbothermal reduction using a vapor-liquid-solid mechanism inside a chemical vapor deposition (CVD) furnace. The nanostructures have been structurally and optically characterized using X-ray diffraction, scanning and transmission electron microscopy and related techniques as well as photoluminescence, confirming their crystalline nature. To study the gas sensing properties of the nanowires, they have been removed from the substrates where they grew applying sonication, followed by the deposition on a silicon substrate with suspended microhotplates that contain integrated heater and prepatterned electrodes, and have been further contacted by Focused Electron- and Focused Ion-Beam techniques. The testing of the device towards ethanol at different concentrations and temperatures in synthetic gas has been carried out showing good responses at temperatures between 200 and 300 °C.